우리나라 소나무 주요유형지별 식생구조와 환경요인 - 윤정원; 김용식; 김기송; 성정원; 박기환; 이창현; 신현탁; 이명훈 (Journal of forest and environmental science , 30(1), 2014)
The populations of Pinus densiflora in South Korea were grouped into 4 types; Community of Pinus densiflora-Quercus serrata, Community of Pinus densiflora-Quercus mongolica, Community of Pinus densiflora-Fraxinus sieboldiana & Rhus javanica & Quercus mongolica and Community of Pinus densiflora-Prunus sargentii & Rhododendron mucronulatum. The Shannon diversity index was varied between 0.9171 and 1.5016, while the Similarity index was varied between 43.18 and 72.16. The species of Pinus densiflora are correlated positively significant with Carex humilis var. nana, Quercus serrata and Atractylodes ovata and negatively significant with Aster scaber and Sorbus alnifolia in order. According to the Correlation analysis, the relationship between the distribution of Pinus densiflora populations and the environment factors are closely related with the character of forest soil. Thus types for Pinus densiflora are differed. pH, Ex. K and Ex. Ca of Pinus densiflora populations effect No. of species and H’(shannon index). Canopy open effects No. of Individuals of Pinus densiflora community. KCI Citation Count: 0